Automated Oxygen Gradient Ektacytometry: A Novel Biomarker in Sickle Cell Anemia - Sadaf, Alina; Seu, Katie G.; Thaman, Elizabeth; Fessler, Rose; Konstantinidis, Diamantis G.; Bonar, Holly A.; Korpik, Jennifer; Ware, Russell E.; McGann, Patrick T.; Quinn, Charles T.; Kalfa, Theodosia A. (Frontiers in Physiology, 2021)
Sickle cell anemia (SCA) is a hereditary hemoglobinopathy with a variable phenotype. There is no single biomarker that adequately predicts disease severity and can be used to monitor treatment response in patients in clinical trials and clinical care. The use of clinical outcomes such as vaso-occlusive crises (VOC) requires long and expensive studies, sometimes with inconclusive results. To address these limitations, there are several biomarkers under study to improve the ability to predict complications and assess treatment response in both clinical and research settings. Oxygen gradient ektacytometry, also called oxygenscan, is an assay that measures the effects of deoxygenation and reoxygenation on red blood cell (RBC) deformability and is gaining popularity in SCA research, because it captures the dynamic sickling capacity of a patient’s RBCs as they are subjected to an oxygen gradient under steady shear stress. We describe here the oxygenscan methodology and evaluate the correlation between oxygenscan parameters and more well-known biomarkers of SCA such as fetal hemoglobin (HbF), F-cells, and dense red blood cells (DRBCs). Our data indicate that the oxygenscan curve is affected by all these parameters and the result incorporates the effects of %HbF, %F-cells, RBC hydration, and RBC membrane deformability.